Light‐Controlled, High‐Resolution Patterning of Living Engineered Bacteria Onto Textiles, Ceramics, and Plastic. (27th May 2019) - Moser, Felix; Tham, Eléonore; González, Lina M.; Lu, Timothy K.; Voigt, Christopher A.
Abstract: Living cells can impart materials with advanced functions, such as sense‐and‐respond, chemical production, toxin remediation, energy generation and storage, self‐destruction, and self‐healing. Here, an approach is presented to use light to pattern Escherichia coli onto diverse materials by controlling the expression of curli fibers that anchor the formation of a biofilm. Different colors of light are used to express variants of the structural protein CsgA fused to different peptide tags. By projecting color images onto the material containing bacteria, this system can be used to pattern the growth of composite materials, including layers of protein and gold nanoparticles. This is used to pattern cells onto materials used for 3D printing, plastics (polystyrene), and textiles (cotton). Further, the adhered cells are demonstrated to respond to sensory information, including small molecules (IPTG and DAPG) and light from light‐emitting diodes. This work advances the capacity to engineer responsive living materials in which cells provide diverse functionality. Abstract : Bacteria are engineered to generate biofilm materials in response to three colors of light. These biofilms could be precisely patterned on diverse materials, including wearable fibers. Cells embedded in the biofilm remain alive and responsive to light and chemical signals. By altering the color of the incident light, the composition of the biofilm material could be finely tuned.